Ecocritical analysis of “glocal” essays on Lived Experiences of Climate Change in higher education - van Herten, Marjolein; Perez, Paquita (Frontiers in Sustainability, 2022)
Being a ‘super wicked problem’, climate change deserves a multidisciplinary approach in higher education that actively engages students with this global subject that has local and regional consequences as well. The online Short Learning Program ‘Climate change: from global to local action’ combines environmental scientific, economic and social knowledge. With the conceptual model of Lived Experience of Climate Change (LivExpCC), it aims at engaging students with climate change and explicitly adds the human dimension. In the final assignment, students write an essay, in which they connect their personal and local experiences with regional, proximate influences and with broader global contextual influences of climate change, which stimulates the knowledge-reflection-engagement-action cycle The essays are analyzed with ecocritical and storytelling techniques, such as referentiality, spatial distances, temporal distances, and whether the narrative is utopian or dystopian. We investigate how through these narratives the students engage with climate change, using their local lived experiences. With an ecocritical lens we observe that limited local distances and vivid inherited histories, show that these students are well aware of the effects of climate change, and engage with it in different ways.